2008
DOI: 10.1021/tx800104c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon- and Oxygen-Centered Radicals Are Equally Important Haptens of Allylic Hydroperoxides in Allergic Contact Dermatitis

Abstract: Limonene is one of the most commonly used fragrance compounds in western countries today. When exposed to air, it autoxidises, forming hydroperoxides that are strong contact allergens. To cause allergic contact dermatitis (ACD), the hydroperoxides are considered to bind covalently to proteins in the skin via a radical pathway. Consequently, the nature and reactions of the radicals formed from the hydroperoxides are important. We have examined the radical formation from, and sensitizing potential of, three ally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(89 citation statements)
references
References 51 publications
(96 reference statements)
11
78
0
Order By: Relevance
“…1 H-and 13 C-NMR data of LinOOH 1, and LinOAcOOH 2 (both in a 5:3 ratio of tertiary hydroperoxide/secondary hydroperoxide) and LimOOH 3 agree with literature data [16,23,24].…”
Section: Nmr Spectroscopysupporting
confidence: 87%
See 1 more Smart Citation
“…1 H-and 13 C-NMR data of LinOOH 1, and LinOAcOOH 2 (both in a 5:3 ratio of tertiary hydroperoxide/secondary hydroperoxide) and LimOOH 3 agree with literature data [16,23,24].…”
Section: Nmr Spectroscopysupporting
confidence: 87%
“…The monoterpenes were purified by distillation (≥97% according to GC/MS) before use. The hydroperoxides were synthesized and purified according to earlier experience [16,23,24]. Identity and purity of the analytes were examined with NMR (>96% purity), and the data agreed with published reports.…”
Section: Chemicalssupporting
confidence: 64%
“…A large fraction of this literature focuses on the allergenic properties of limonene, which were shown to be due to limonene hydroperoxide (25,(36)(37)(38). This direct parallel to bacterial toxicity suggests a general cellular damage mechanism for limonene hydroperoxide.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The sensitizing potency based on the murine local lymph node assay (LLNA) is categorized into extreme (EC3 value of ≤0.2%), strong (>0.2% to ≤2%), and moderate (>2%). 14 The allylic hydroperoxides derived from air-oxidized linalool, 15 limonene, 16 and citronellol, 17 as well as the other air-oxidized compounds, were evaluated in the LLNA, and the results showed that the hydroperoxides are the most potent sensitizers among all oxidation products derived from air oxidation of the parent terpenes. Consequently, limonene- 16 and the mixture of linalool hydroperoxides 15 are categorized as strong sensitizers, and the mixture of citronellol hydroperoxides is classified as a moderate sensitizer 17 (Table 2).…”
Section: Introductionmentioning
confidence: 99%